2009
DOI: 10.1111/j.1469-8986.2009.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Parsing the componential structure of post‐error ERPs: A principal component analysis of ERPs following errors

Abstract: We report the results of two experiments designed to clarify the spatial and temporal characteristics of the positive deflection that follows the error related negativity (ERN) elicited to incorrect responses in speeded reaction time tasks. Principal components analysis (PCA) indicates that the positive deflection reported to follow the ERN is composed of two different components: (a) a fronto-central positive deflection that follows the ERN and shares its spatial distribution and (b) a P300. When accuracy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 33 publications
9
65
1
6
Order By: Relevance
“…This ''error-positivity'' (Pe), generally thought to reflect awareness of the error, was originally described by Falkenstein, Hohnsbein, Hoormann, and Blanke (1991) as an amalgam of two overlapping positive components, one closely associated with and perhaps part of the ERN, and the second a P300 associated with orienting (Overbeek, Nieuwenhuis, & Ridderinkhof, 2005). This composite structure has been substantiated recently by Donchin and his colleagues (Arbel & Donchin, 2009) via spatial-temporal principal components analysis (PCA). Finally, Figure 1 also reflects the occurrence of a small negative deflection associated with the execution of correct responses.…”
Section: Introductionmentioning
confidence: 93%
“…This ''error-positivity'' (Pe), generally thought to reflect awareness of the error, was originally described by Falkenstein, Hohnsbein, Hoormann, and Blanke (1991) as an amalgam of two overlapping positive components, one closely associated with and perhaps part of the ERN, and the second a P300 associated with orienting (Overbeek, Nieuwenhuis, & Ridderinkhof, 2005). This composite structure has been substantiated recently by Donchin and his colleagues (Arbel & Donchin, 2009) via spatial-temporal principal components analysis (PCA). Finally, Figure 1 also reflects the occurrence of a small negative deflection associated with the execution of correct responses.…”
Section: Introductionmentioning
confidence: 93%
“…Several experiments have supported this prediction. For example, studies have found increased ERN amplitudes when accuracy is emphasized over speed (Arbel & Donchin, 2009;Falkenstein, Hoormann, Christ, & Hohnsbein, 2000;Gehring et al, 1993) and when the stimuli are bright (Yeung, Ralph, & Nieuwenhuis, 2007). These conditions are thought to increase the tendency to respond correctly, and when errors are committed, the two response tendencies (error and correct) conflict with one another, producing larger ERN amplitudes.…”
mentioning
confidence: 99%
“…Sin ser necesariamente excluyentes entre sí, las tres hipótesis dominantes sobre el significado funcional del Pe proponen que dicho componente refleja (a) la evaluación emocional de los errores o sus consecuencias, (b) el reconocimiento consciente de la comisión de un error, y/o (c) la adaptación de las estrategias de respuesta tras la percepción de la comisión de un error (Falkenstein, 2004;Overbeek y cols., 2005). Aunque posteriormente se revisará la evidencia empírica que respalda dichas hipótesis, actualmente existen cierto debate acerca de si el Pe -que puede ser observado en todos los sensores de la línea media-refleja un proceso unitario o puede ser subdividido en dos componentes: uno más temprano y ligado al ERN (early-Pe) con una distribución frontocentral máxima, y otro posterior y más sostenido en el tiempo (late-Pe) con una distribución centroparietal máxima (Arbel y Donchin, 2009;van Veen y Carter, 2002a).…”
Section: El Componente Error Positivity (Pe)unclassified
“…Es relevante para la subdivisión del componente Pe en la parte 'temprana' y 'tardía' el hecho de que algunos estudios de localización de fuentes hayan mostrado que la parte temprana del Pe que sigue al ERN en áreas frontocentrales parece explicada por los mismos generadores situados en la parte dorsal de la ACC, mientras que los generadores neurales propuestos para el componente Pe 'tardío' en sensores centroparietales parecen situarse en las áreas rostrales de la ACC y de la corteza parietal comentadas anteriormente (O'Connell y cols., 2007; van Veen y Carter, 2002a). Sin embargo, esta división del componente Pe no ha predominado en la literatura hasta la fecha, y sólo recientemente se han empezado a aplicar otras técnicas de aná-lisis, como el análisis de componentes principales temporo-espacial, para subdividir el componente Pe (Arbel y Donchin, 2009;Endrass, Klawohn, Preuss y Kathmann, 2012). Mediante la aplicación de estas técnicas se han identificado dos componentes que son consistentes con la distinción entre el Pe 'temprano' y 'tardío': (1) un componente con una distribución centroparietal y latencia tardía, máximo a partir de los 300 ms tras la comisión de un error, que parece consistentemente asociado a la consciencia de los errores (Endrass y cols., 2012) y también a manipulaciones que afectan a la importancia de responder de forma precisa (Arbel y Donchin, 2009); y (2) otro componente que comparte la distribución topográfica máxima del ERN en áreas frontocentrales y latencia más temprana que no es sensible a dichas manipulaciones.…”
Section: El Componente Error Positivity (Pe)unclassified
See 1 more Smart Citation